Yupingfeng polysaccharide promote the growth of chickens via regulating gut microbiota - Guan, Yuling; Zheng, Wendan; Bai, Yu; Wu, Bo (Frontiers in Veterinary Science, 2024)
Yupingfeng polysaccharide (YPF-P) is the main substance of alcohol deposition in Yupingfeng powder, which has many biological functions such as enhancing immunity, repairing intestinal barrier and enhancing antioxidant ability. This study employed in vitro growth-promoting drug feed additives and animal experiments to comprehensively evaluate the use of YPF-P in broiler production. A total of 1296 151-day-old Qingyuan Partridge chickens were randomly divided into four groups with six replicates and 54 hens per replicate: the control group was fed basal diet, and the experimental groups were fed diets supplemented with 4 g/kg, 8 g/kg, and 12 g/kg YPF-P for 14 days. Broilers were weighed before and at the end of the experiment to calculate total weight gain(GW), average daily gain(ADG), and feed compensation. At the end of the experiment, six chickens from each group were randomly selected for subwing vein blood sampling, which was used to measure serum biochemical indicators GHRH, GH and IGF-1 by ELISA method. Randomly select chickens from control group and 8 g/kg group for slaughter, and cecal contents were collected for 16S high-throughput sequencing. The results show as follows: Dietary supplementation of 8 g/kg YPF-P can significantly increase the final body weight, total weight gain, average daily gain and decrease the feed to gain ratio of chickens. During 151-165 days, serum IGF-1 concentrations increased significantly (p < 0.05). There were no significant changes in serum GH concentration (p > 0.05). In terms of gut microbiota, there was no significant difference between control group and test group in Shannon index and Simpson index. Compared with the control group, the addition of 8 g/kgYPF-P significantly increased the abundance of Firmicutes and significantly decreased the abundance of Bacteroides at the phylum level. At the genus level, the relative abundance of unclassified_Oscillospiraceae was significantly increased and the unclassified_Muribaculaceae, uncultured _ Bacteroidales _bacterium, Lactobacillus, Alloprevotella, Ligilactobacillus, Prevotellaceae_UCG_001, and unclassified_Atopobiaceae was significantly decreased. The above results showed that adding 8 mg/kg of YPF-P could increase the average daily gain of Qingyuan Partridge chickens, reduce the ratio of feed to meat, and affect the distribution proportion of intestinal microflora in chickens to some extent.